Tenecteplase versus alteplase before endovascular thrombectomy (EXTEND-IA TNK): A multicenter, randomized, controlled study. Issue 3 (April 2018) - Campbell, Bruce CV; Mitchell, Peter J; Churilov, Leonid; Yassi, Nawaf; Kleinig, Timothy J; Yan, Bernard; Dowling, Richard J; Bush, Steven J; Dewey, Helen M; Thijs, Vincent; Simpson, Marion; Brooks, Mark; et al.
Background and hypothesis: Intravenous thrombolysis with alteplase remains standard care prior to thrombectomy for eligible patients within 4.5 h of ischemic stroke onset. However, alteplase only succeeds in reperfusing large vessel arterial occlusion prior to thrombectomy in a minority of patients. We hypothesized that tenecteplase is non-inferior to alteplase in achieving reperfusion at initial angiogram, when administered within 4.5 h of ischemic stroke onset, in patients planned to undergo endovascular therapy. Study design: EXTEND-IA TNK is an investigator-initiated, phase II, multicenter, prospective, randomized, open-label, blinded-endpoint non-inferiority study. Eligibility requires a diagnosis of ischemic stroke within 4.5 h of stroke onset, pre-stroke modified Rankin Scale≤3 (no upper age limit), large vessel occlusion (internal carotid, basilar, or middle cerebral artery) on multimodal computed tomography and absence of contraindications to intravenous thrombolysis. Patients are randomized to either IV alteplase (0.9 mg/kg, max 90 mg) or tenecteplase (0.25 mg/kg, max 25 mg) prior to thrombectomy. Study outcomes: The primary outcome measure is reperfusion on the initial catheter angiogram, assessed as modified treatment in cerebral infarction 2 b/3 or the absence of retrievable thrombus. Secondary outcomes include modified Rankin Scale at day 90 and favorable clinical response (reduction in National Institutes of Health Stroke Scale by ≥8 points or reaching 0–1) at day 3. Safety outcomes are death and symptomatic intracerebral hemorrhage. Trial registration: ClinicalTrials.gov NCT02388061